2013
DOI: 10.1016/j.jamcollsurg.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Late Recurrence in Melanoma: Clinical Implications of Lost Dormancy

Abstract: Background For patients with melanoma, if there has been no recurrence of disease 10 years after initial treatment, additional disease is felt to be very unlikely. However, such late recurrence are known to occur. The frequency of this phenomenon and its clinical significance are not well characterized due to the difficulty in obtaining relevant data. We examined a large, mature, institutional database to evaluate late recurrence. Study Design The late recurrence cohort was defined as having a DFI of ≥10 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
66
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(75 citation statements)
references
References 30 publications
3
66
0
6
Order By: Relevance
“…Any remaining differences in the frequency of nodal metastasis may be accounted for by chance or by late nodal recurrences still pending in the observation group. 31,32 These data indicate that essentially all metastases detected by sentinel-node biopsy eventually would have become clinically evident if not removed.…”
Section: Discussionmentioning
confidence: 89%
“…Any remaining differences in the frequency of nodal metastasis may be accounted for by chance or by late nodal recurrences still pending in the observation group. 31,32 These data indicate that essentially all metastases detected by sentinel-node biopsy eventually would have become clinically evident if not removed.…”
Section: Discussionmentioning
confidence: 89%
“…8 Conversely, in patients with nonYsmall cell lung cancer, 10.6% (87/819) of the patients with no recurrence at 5 years after diagnosis subsequently developed recurrence. 9 Yet, in another study, late recurrence beyond 10 years was observed in 327 (6.9%) of 4731 patients, 10 whereas recurrence beyond 5 years for colorectal cancer was reported in 36 (0.89%) of 4023 cases. 11 In the current study, the rate of recurrence beyond 5 years after curative surgery was 1.0%.…”
Section: Discussionmentioning
confidence: 94%
“…Patients facing late recurrence were typically younger, with an average age of 41 to an average of 51 for early recurrence of melanoma [22, 23]. Studies have shown that sunscreen use decreases the incidence of sunburns.…”
Section: Discussionmentioning
confidence: 99%